Towards the understanding of the enzymatic cleavage of polyisoprene by the dihaem-dioxygenase RoxA - Schmitt, Georg (AMB Express, 2019)
Utilization of polyisoprene (natural rubber) as a carbon source by Steroidobacter cummioxidans 35Y (previously Xanthomonas sp. strain 35Y) depends on the formation and secretion of rubber oxygenase A (RoxA). RoxA is a dioxygenase that cleaves polyisoprene to 12-oxo-4,8-dimethyl-trideca-4,8-diene-1-al (ODTD), a suitable growth substrate for S. cummioxidans. RoxA harbours two non-equivalent, spectroscopically distinguishable haem centres. A dioxygen molecule is bound to the N-terminal haem of RoxA and identifies this haem as the active site. In this study, we provide insights into the nature of this unusually stable dioxygen-haem coordination of RoxA by a re-evaluation of previously published together with newly obtained biophysical data on the cleavage of polyisoprene by RoxA. In combination with the meanwhile available structure of RoxA we are now able to explain several uncommon and previously not fully understood features of RoxA, the prototype of rubber oxygenases in Gram-negative rubber-degrading bacteria.